Unveiling the TPACK profile: Exploring mathematics prospective teachers in the micro teaching course - Sartika, Nenden Suciyati; Munawaroh, Tatu; Meika, Ika; Mauladaniyati, Ratu; Yunitasari, Ika; Sahrudin, Asep; Sujana, Asep; Rosdianwinata, Eka; Pratidiana, Deni; Mulyanah, Mulyanah; Rifa'i, Rusdian (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2023)
The objective of this research is to ascertain the Technological Pedagogical Content Knowledge (TPACK) profile of prospective mathematics teachers in the microteaching course. The research methodology employed a survey research design. The target population for this investigation comprises prospective mathematics teacher students enrolled at a University in Banten, Indonesia. The sample for this study comprises students in their sixth semester of the Mathematics Education program who are currently enrolled in the microteaching course. The inclusion criteria for the sample require that these students have successfully completed coursework in foundational technology use, pedagogical principles, and both basic and advanced mathematics subjects. The research findings indicate that the majority of students exhibit a high level of Technological Content Knowledge (TCK) and Technological Pedagogical and Content Knowledge (TPACK), with percentages of 50% and 81.25% respectively. On the other hand, the majority of students demonstrate a moderate level of Pedagogical Knowledge (PK) and Technological Pedagogical Knowledge (TPK), with percentages of 56.25% and 31.25% respectively. Moreover, a significant portion of students show a low level of Technological Knowledge (TK) at 31.25%, Content Knowledge (CK) at 37.5%, and Pedagogical Content Knowledge (PCK) at 37.5%. It conluded, most prospective tezchers use the Technological Conten Knowledge (TCK) and Technological Pedagogical and Content Knowledge (TPACK) domains to conduct learning.